The two red flags : European social democracy and Soviet communism since 1945 - Childs, David, 1933- (Routledge, 2000)
An incisive account of the impact of socialism on the life and politics of Europe and the former Soviet bloc in the twentieth century. It covers the origins of socialism in those countries where it had most impact.